Hydroxyl-rich nanoporous carbon nanosheets synthesized by a one-pot method and their application in the in situ preparation of well-dispersed Ag nanoparticles. Issue 116 (9th November 2015) - Guo, Xiaodi; Liu, Gaili; Yue, Shuang; He, Jing; Wang, Lianying
Abstract : Nanoporous carbon nanosheets (CNSs) with high surface area have been synthesized by pyrolysis of organic–inorganic precursor. The CNSs with rich hydroxyl groups display remarkable reactivity and capability for in situ loading ultrafine Ag NPs. Abstract : Functional nanoporous carbon nanosheets (CNSs) with high surface areas have been synthesized by the pyrolysis of simple organic–inorganic layered zinc hydroxide nanosheets. The synthesized CNSs with abundant hydroxyl groups display remarkable reactivity and the capability for in situ loading with ultrafine Ag NPs, which show excellent catalytic activity toward the reduction of 4-nitrophenol (4-NP) by NaBH4 .